Preparation method and application of biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheet composite photocatalyst
By coupling biomass nitrogen-doped carbon quantum dots with BiOBr ultra-thin nanosheets, a photocatalyst of BiOBr@NCQDs composite material is formed, which solves the problems of low light absorption edges of traditional photocatalysts and fast electron-hole pair recombination rate, achieving efficient visible light utilization and rapid degradation of organic dyes, and has good cycling stability.
Patent Information
- Application Number
- CN202310094165.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-02-10
AI Technical Summary
The traditional TiO2 photocatalysts have limited their photocatalytic performance due to their large band-discharge width, low visible light utilization rate and easy recombination of electron-hole pairs. The existing BiOBr photocatalysts have also limited their actual application due to their low light absorption edge and fast electron-hole pair recombination rate.
Biomass nitrogen-doped carbon quantum dots (NCQDs) are used to couple with BiOBr ultra-thin nanosheets to form the composite photocatalyst BiOBr@NCQDs. This method significantly improves the utilization rate of visible light and suppresses the recombination of electron-hole pairs.
It significantly improves the utilization rate of visible light, effectively inhibits the recombination of electron-hole pairs, has a good degradation efficiency for organic dyes in industrial wastewater, and has a 99% degradation efficiency for rhodamine B within 20 minutes, and has good cycling stability.
Smart Images

Figure CN116196944B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysts, and in particular relates to a preparation method and application of a biomass nitrogen-doped carbon quantum dot coupled ultrathin BiOBr nanosheet composite material photocatalyst. Background Art
[0002] With the rapid development of global economy and industrialization, a large amount of toxic and harmful wastewater is directly discharged into natural water bodies, which seriously affects human health and ecological balance. Semiconductor photocatalytic technology is considered to be an environmentally friendly technology to solve environmental problems and energy shortages due to its advantages of being green, efficient, and directly using inexhaustible solar energy as a driving force. 2 The photocatalytic performance of traditional photocatalysts is limited by their large bandgap, low visible light utilization, and easy recombination of photogenerated electron-hole pairs. Therefore, the design and development of efficient visible light-responsive photocatalysts has become a frontier issue in current research.
[0003] As a typical bismuth-based semiconductor photocatalytic material, BiOBr is widely used in the field of photocatalysis due to its suitable bandgap, high visible light response, unique layered structure and excellent chemical stability. However, the low light absorption edge and fast electron-hole pair recombination rate greatly limit its practical application. In order to improve the photocatalytic performance of BiOBr, the construction of BiOBr composite materials is a current research hotspot in the field of photocatalysis. Carbon materials are often used in the composite of photocatalytic materials, which can effectively inhibit the recombination of electron-hole pairs to improve the photocatalytic activity. However, the development of biomass-based nitrogen-carbon quantum dot composite BiOBr composite photocatalytic materials has rarely been reported. Summary of the invention
[0004] The present invention overcomes the deficiencies of the prior art and provides a method for preparing a biomass nitrogen-doped carbon quantum dot coupled ultrathin BiOBr nanosheet composite material photocatalyst.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0006] 1. A method for preparing a biomass nitrogen-doped carbon quantum dot coupled ultrathin BiOBr nanosheet composite photocatalyst, comprising the following steps:
[0007] a. Preparation of biomass nitrogen-doped carbon quantum dots:
[0008] Grapefruit peel with surface dust removed was selected as a biomass carbon source, which was dried and ground into fine particles. The sample was then mixed evenly with potassium hydroxide and urea, and the mixed sample was calcined under a nitrogen atmosphere. The calcined sample was washed with HCl solution and deionized water, and then dried to obtain nitrogen-doped carbon quantum dots NCQDs.
[0009] b. Preparation of nitrogen-doped carbon quantum dots coupled with BiOBr ultrathin nanosheet composite photocatalyst:
[0010] Bismuth nitrate was added to anhydrous methanol under magnetic stirring, and then potassium bromide and polyvinyl pyrrolidone were added to the anhydrous methanol solution of bismuth nitrate in sequence under continuous stirring and stirred for 30 min to obtain solution A; a certain amount of nitrogen-doped carbon quantum dots were dispersed in deionized water and ultrasonicated for 10 min to obtain solution B; then, solution B was added dropwise to solution A and stirred at room temperature for 30 min, and the obtained solution was transferred to a reactor. After the heating reaction was completed, the obtained product was centrifuged, washed and dried to obtain the biomass nitrogen-doped carbon quantum dots coupled BiOBr ultra-thin nanosheets composite material photocatalyst BiOBr@NCQDs.
[0011] Furthermore, in the above scheme, the mass ratio of the grapefruit peel particle sample to potassium hydroxide and urea in step a is 3:1:1.
[0012] Furthermore, in the above scheme, the drying condition of the grapefruit peel in step a is 120 o C for 4 h; the mixed sample was calcined under nitrogen atmosphere at 150 o C. 300 o C and 800 o The temperature sequence was 0.5-1.5 h, and the concentration of the HCl solution used to wash the samples after calcination was 1 mol L −1 .
[0013] Furthermore, in the above scheme, in step b, the molar amount of bismuth nitrate is 2.5-3.5 mmol; and the molar ratio of bismuth nitrate to potassium bromide is 1:1.
[0014] Furthermore, in the above scheme, in step b, the mass volume ratio of polyvinyl pyrrolidone to anhydrous methanol is 0.05 - 0.15 g: 35 mL.
[0015] Furthermore, in the above scheme, in step b, the mass of the nitrogen-doped carbon quantum dots is 1%-7% of the mass of the bismuth oxybromide.
[0016] Further, in the above scheme, in step b, the reaction conditions of the mixed solution in the reactor are 150 o C-160 o C, heating for 10 - 12 h.
[0017] In addition, the present invention also provides the use of the biomass nitrogen-doped carbon quantum dots coupled ultra-thin BiOBr nanosheet composite material photocatalyst obtained by the above preparation method in wastewater treatment.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The bismuth oxybromide and biomass carbon materials in the present invention are both relatively stable, environmentally friendly, will not cause secondary pollution, and have a certain degree of recyclability.
[0020] 2. The composite material prepared in the present invention has cheap and readily available synthetic raw materials, mild preparation conditions, simple operation, stable product quality, easy control of various parameters, high production efficiency, and easy to achieve large-scale production.
[0021] 3. The biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheets composite photocatalyst prepared by the present invention significantly improves the utilization rate of visible light, effectively inhibits the recombination of electron-hole pairs, has a good degradation efficiency for organic dyes in industrial wastewater, and the degradation efficiency of rhodamine B (RhB) reaches 99% within 20 minutes, and has good cycle stability. Therefore, it has a good application prospect in the field of photocatalysis and wastewater treatment, and is expected to be used for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD diagrams of biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheet composite material photocatalysts prepared in Examples 1 to 4 of the present invention.
[0023] Figure 2 The microscopic morphology of the biomass nitrogen-doped carbon quantum dots coupled with ultra-thin BiOBr nanosheet composite material photocatalyst prepared in Examples 1 to 4 of the present invention, wherein (a) is m NCQDs : m BiOBr = 1 %, (b) is m NCQDs : m BiOBr = 3%, (c) is m NCQDs : m BiOBr = 5%, (d) is m NCQDs : m BiOBr = 7 %.
[0024] Figure 3 TEM and HRTEM images of the biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheet composite material photocatalyst prepared in Example 3 of the present invention.
[0025] Figure 4 The UV-visible absorption spectra of the biomass nitrogen-doped carbon quantum dots coupled ultrathin BiOBr nanosheet composite material photocatalyst and bismuth oxybromide obtained in Examples 1 to 4 of the present invention.
[0026] Figure 5Band gap diagrams of biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheet composite material photocatalyst and bismuth oxybromide obtained in Examples 1 to 4 of the present invention.
[0027] Figure 6 The degradation curves of Rhodamine B under visible light conditions are shown in Figure 2, which are obtained by using a composite photocatalyst without photocatalyst, pure BiOBr, and biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheets at different mass ratios prepared in Examples 1 to 4.
[0028] Figure 7 This is a cyclic stability diagram of the biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheets composite material photocatalyst prepared in Example 3 of the present invention. Implementation
[0029] The present invention is further described below in conjunction with specific embodiments. Example
[0030] A method for preparing a biomass nitrogen-doped carbon quantum dot coupled ultrathin BiOBr nanosheet composite material photocatalyst comprises the following steps:
[0031] a) Preparation of biomass nitrogen-doped carbon quantum dots:
[0032] 1) Wash the grapefruit peels several times with deionized water to remove surface dust, then o C drying for 4 h;
[0033] 2) The dried sample was ground into fine particles, then the sample was evenly mixed with potassium hydroxide and urea (mass ratio of 3:1:1), and the mixed sample was calcined under nitrogen atmosphere at 150 o C. 300 o C and 800 o C temperature sequence was kept for 1 h;
[0034] 3) In order to remove impurities, the calcined sample was treated with 1 mol L −1 HCl and deionized water, then heated at 120 o C for 4 h, and the final product is nitrogen-doped carbon quantum dots (NCQDs).
[0035] b) Preparation of nitrogen-doped carbon quantum dots coupled with BiOBr ultrathin nanosheets:
[0036] 1) Take 3 mmol of bismuth nitrate and add it to 35 mL of anhydrous methanol under magnetic stirring, and stir until dissolved;
[0037] 2) 3 mmol of potassium bromide and 0.1 g of polyvinyl pyrrolidone were added to the above solution in sequence under continuous stirring and stirred for 30 min to obtain solution A;
[0038] 3) Dispersing nitrogen-doped carbon quantum dots accounting for 1% of the mass of bismuth oxybromide in 15 mL of deionized water, and ultrasonicating for 10 min to obtain solution B;
[0039] 4) Add solution B dropwise into solution A and stir at room temperature for 30 min;
[0040] 5) Transfer the above solution into a 100 mL reactor and heat at 160 o C for 12 h;
[0041] 6) After the reaction is completed, the reactor is taken out, cooled, and the sample is taken out. The obtained product is centrifuged, washed, and dried to obtain a nitrogen-doped carbon quantum dot-coupled BiOBr ultrathin nanosheet composite material photocatalyst. Example
[0042] A method for preparing a biomass nitrogen-doped carbon quantum dot coupled ultrathin BiOBr nanosheet composite material photocatalyst comprises the following steps:
[0043] a) Preparation of biomass nitrogen-doped carbon quantum dots:
[0044] 1) Wash the grapefruit peels several times with deionized water to remove surface dust, then o C drying for 4 h;
[0045] 2) The dried sample was ground into fine particles, then the sample was evenly mixed with potassium hydroxide and urea (mass ratio of 3:1:1), and the mixed sample was calcined under nitrogen atmosphere at 150 o C. 300 o C and 800 o C temperature sequence was kept for 1 h;
[0046] 3) In order to remove impurities, the calcined sample was treated with 1 mol L −1 HCl and deionized water, then heated at 120 o C for 4 h, and the final product is nitrogen-doped carbon quantum dots (NCQDs).
[0047] b) Preparation of nitrogen-doped carbon quantum dots coupled with BiOBr ultrathin nanosheets:
[0048] 1) Take 3 mmol of bismuth nitrate and add it to 35 mL of anhydrous methanol under magnetic stirring, and stir until dissolved;
[0049] 2) 3 mmol of potassium bromide and 0.1 g of polyvinyl pyrrolidone were added to the above solution in sequence under continuous stirring and stirred for 30 min to obtain solution A;
[0050] 3) Dispersing nitrogen-doped carbon quantum dots with a mass ratio of 3% of bismuth oxybromide in 15 mL of deionized water, and ultrasonicating for 10 min to obtain solution B;
[0051] 4) Add solution B dropwise into solution A and stir at room temperature for 30 min;
[0052] 5) Transfer the above solution into a 100 mL reactor and heat at 160 o C for 12 h;
[0053] 6) After the reaction is completed, the reactor is taken out, cooled, and the sample is taken out. The obtained product is centrifuged, washed, and dried to obtain a nitrogen-doped carbon quantum dot-coupled BiOBr ultrathin nanosheet composite material photocatalyst. Example
[0054] A method for preparing a biomass nitrogen-doped carbon quantum dot coupled ultrathin BiOBr nanosheet composite material photocatalyst comprises the following steps:
[0055] a) Preparation of biomass nitrogen-doped carbon quantum dots:
[0056] 1) Wash the grapefruit peels several times with deionized water to remove surface dust, then o C drying for 4 h;
[0057] 2) The dried sample was ground into fine particles, then the sample was evenly mixed with potassium hydroxide and urea (mass ratio of 3:1:1), and the mixed sample was calcined under nitrogen atmosphere at 150 o C. 300 o C and 800 o C temperature sequence was kept for 1 h;
[0058] 3) In order to remove impurities, the calcined sample was treated with 1 mol L −1 HCl and deionized water, then heated at 120 o C for 4 h, and the final product is nitrogen-doped carbon quantum dots (NCQDs).
[0059] b) Preparation of nitrogen-doped carbon quantum dots coupled with BiOBr ultrathin nanosheets:
[0060] 1) Take 3 mmol of bismuth nitrate and add it to 35 mL of anhydrous methanol under magnetic stirring, and stir until dissolved;
[0061] 2) 3 mmol of potassium bromide and 0.1 g of polyvinyl pyrrolidone were added to the above solution in sequence under continuous stirring and stirred for 30 min to obtain solution A;
[0062] 3) Dispersing nitrogen-doped carbon quantum dots with a mass ratio of 5% to bismuth oxybromide in 15 mL of deionized water, and ultrasonicating for 10 min to obtain solution B;
[0063] 4) Add solution B dropwise into solution A and stir at room temperature for 30 min;
[0064] 5) Transfer the above solution into a 100 mL reactor and heat at 160 o C for 12 h;
[0065] 6) After the reaction is completed, the reactor is taken out, cooled, and the sample is taken out. The obtained product is centrifuged, washed, and dried to obtain a nitrogen-doped carbon quantum dot-coupled BiOBr ultrathin nanosheet composite material photocatalyst. Example
[0066] A method for preparing a biomass nitrogen-doped carbon quantum dot coupled ultrathin BiOBr nanosheet composite material photocatalyst comprises the following steps:
[0067] a) Preparation of biomass nitrogen-doped carbon quantum dots:
[0068] 1) Wash the grapefruit peels several times with deionized water to remove surface dust, then o C drying for 4 h;
[0069] 2) The dried sample was ground into fine particles, then the sample was evenly mixed with potassium hydroxide and urea (mass ratio of 3:1:1), and the mixed sample was calcined under nitrogen atmosphere at 150 o C. 300 o C and 800 o C temperature sequence was kept for 1 h;
[0070] 3) In order to remove impurities, the calcined sample was treated with 1 mol L −1 HCl and deionized water, then heated at 120 o C for 4 h, and the final product is nitrogen-doped carbon quantum dots (NCQDs).
[0071] b) Preparation of nitrogen-doped carbon quantum dots coupled with BiOBr ultrathin nanosheets:
[0072] 1) Take 3 mmol of bismuth nitrate and add it to 35 mL of anhydrous methanol under magnetic stirring, and stir until dissolved;
[0073] 2) 3 mmol of potassium bromide and 0.1 g of polyvinyl pyrrolidone were added to the above solution in sequence under continuous stirring and stirred for 30 min to obtain solution A;
[0074] 3) Dispersing nitrogen-doped carbon quantum dots with a mass ratio of 7% of bismuth oxybromide in 15 mL of deionized water, and ultrasonicating for 10 min to obtain solution B;
[0075] 4) Add solution B dropwise into solution A and stir at room temperature for 30 min;
[0076] 5) Transfer the above solution into a 100 mL reactor and heat at 160 o C for 12 h;
[0077] 6) After the reaction is completed, the reactor is taken out, cooled, and the sample is taken out. The obtained product is centrifuged, washed, and dried to obtain a nitrogen-doped carbon quantum dot-coupled BiOBr ultrathin nanosheet composite material photocatalyst.
[0078] Performance characterization results:
[0079] 1. By Figure 1 It can be seen that the BiOBr@NCQDs composite photocatalytic materials prepared in Examples 1 to 4 of the present invention have good crystallinity and high purity, and no diffraction peak of NCQDs is observed, which may be due to the low content or low crystallinity;
[0080] 2. By Figure 2 It can be seen that the BiOBr@NCQDs composite photocatalytic materials prepared in Examples 1 to 4 of the present invention have good microscopic morphology, presenting a flower-like ultra-thin nanosheet morphology;
[0081] 3. By Figure 3 It can be seen that in the BiOBr@NCQDs composite photocatalytic material prepared in Example 3 of the present invention, the thickness of BiOBr is about 9 nm, and NCQDs has good dispersibility, with an average particle size of about 7.62 nm;
[0082] 4. By Figure 4 It can be seen that the BiOBr@NCQDs composite photocatalytic materials prepared in Examples 1 to 4 of the present invention have significantly increased visible light adsorption capacity compared with simple bismuth oxybromide;
[0083] 5. By Figure 5 It can be seen that the BiOBr@NCQDs composite photocatalytic materials prepared in Examples 1 to 4 of the present invention significantly reduce the band gap compared with simple bismuth oxybromide, which is beneficial to excite electrons, thereby accelerating the photocatalytic reaction.
[0084] 6. By Figure 6 It can be seen that the BiOBr@NCQDs composite photocatalytic materials prepared in Examples 1 to 4 of the present invention significantly improve the degradation efficiency of rhodamine B compared with simple bismuth oxybromide. Among them, when the mass ratio is 3%, the degradation efficiency is the highest, reaching 99% in 20 minutes;
[0085] 7. By Figure 7 It can be seen that the BiOBr@NCQDs composite photocatalytic material prepared in Example 3 of the present invention has good cycle stability, and after five cycles, the photocatalytic performance has not been significantly reduced.
[0086] It should be pointed out that a person skilled in the art can make several improvements and applications without departing from the principles of the present invention, and these improvements and applications are also considered to be within the protection scope of the present invention.
Claims
1. Application of a biomass nitrogen-doped carbon quantum dot coupled ultrathin BiOBr nanosheet composite material photocatalyst to degrade rhodamine B in wastewater, characterized in that: The preparation method of the composite material photocatalyst comprises the following steps: a. Preparation of biomass nitrogen-doped carbon quantum dots: Grapefruit peels with surface dust removed were selected as biomass carbon sources. o C for 4 h and then ground into fine particles. The sample was then mixed with potassium hydroxide and urea and calcined in a nitrogen atmosphere at 150 o C. 300 o C and 800 o C for 0.5-1.5 h, and the calcined samples were heated to a concentration of 1 mol·L −1 HCl solution and deionized water were used for washing, and then dried to obtain nitrogen-doped carbon quantum dots NCQDs; the mass ratio of grapefruit peel particle sample to potassium hydroxide and urea was 3:1:1; b. Preparation of biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheet composite photocatalyst: Bismuth nitrate was added to anhydrous methanol under magnetic stirring, and then potassium bromide and polyvinyl pyrrolidone were added to the anhydrous methanol solution of bismuth nitrate in sequence under continuous stirring and stirred for 30 min to obtain solution A. A certain amount of nitrogen-doped carbon quantum dots were dispersed in deionized water and ultrasonicated for 10 min to obtain solution B. Subsequently, solution B was added dropwise to solution A and stirred at room temperature for 30 min. The obtained solution was transferred to a reactor, and the reaction conditions of the solution in the reactor were 150 o C-160 o C, heated for 10-12 h. After the heating reaction, the obtained product was centrifuged, washed and dried to obtain the biomass nitrogen-doped carbon quantum dots coupled with ultrathin BiOBr nanosheets composite material photocatalyst BiOBr@NCQDs.
2. The use according to claim 1, characterized in that: In step b, the molar amount of bismuth nitrate is 2.5-3.5 mmol; the molar ratio of bismuth nitrate to potassium bromide is 1:
1.
3. The use according to claim 1, characterized in that: In step b, the mass volume ratio of polyvinyl pyrrolidone to anhydrous methanol is 0.05 - 0.15 g: 35 mL.
4. The use according to claim 1, characterized in that: In step b, the mass of the nitrogen-doped carbon quantum dots is 1%-7% of the mass of the bismuth oxybromide.
Citation Information
Patent Citations
NCQDs / Ru photocatalyst for catalytic reduction of carbon dioxide as well as preparation method and application of NCQDs / Ru photocatalyst
CN111715288A
Preparation method and application of heterojunction nanosheet with two-dimensional ultrathin structure
CN114797910A